(untitled) - Food and Agriculture Organization of the United Nations (Rome, 2008)
This book include: more frequent extreme weather events associated with increasing climate variability and change, agricultural production systems that increa risk, population growth combined with demographic change and movements leading for instance, to unplanning urbanization, growing demand for food, industrial goods and services, and increasing pressure on natural resources.
Dự báo và quản lý thảm họa
Keywords: Disasters,Thiên tai; Risk assessment,Đánh giá rủi ro